Disparities in Access to Driving Licenses as a Barrier to Mobility and Social Participation for Deaf People in the Context of Inclusive Development in Urban Areas - R Yusuf, Reza Pratama; Setiono, Joko; Anggoro, Purwadi Wahyu (Jurnal Greenation Sosial dan Politik, 2025)
This article discusses the disparity in access to driver's licenses for deaf people in Indonesia, which has implications for their limited mobility and social participation in the context of inclusive development in urban areas. Mobility is a constitutionally guaranteed basic right, but in practice, people with hearing disabilities are often faced with structural and administrative barriers when accessing a driver's license. National legal provisions such as Law No. 8 of 2016 on Persons with Disabilities and National Police Regulation No. 5 of 2021 on the Issuance and Marking of Driver's License have not been fully implemented inclusively, especially in the interpretation of hearing health requirements that tend to be discriminatory. The rejection of SIM applications from deaf people, the absence of proper accommodations such as sign language interpreters, and the mismatch between human rights principles and bureaucratic technical procedures indicate an inequality of access rooted in policy bias. This research is a normative juridical approach by analyzing national legislation and international instruments, especially the Convention on the Rights of Persons with Disabilities (CRPD). The analysis shows that barriers to driver's license access limit the participation of deaf people in the economic, educational, and political spheres, and hinder the achievement of inclusive urban development as mandated in the Sustainable Development Goals (SDGs), especially Goal 10 and Goal 11. Policy reforms are needed that emphasize regulatory harmonization, strengthening of reasonable accommodation, and integration of inclusiveness principles in transportation systems and urban planning.